2018
DOI: 10.1530/rep-17-0535
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of male mice after hypothalamic ghrelin administration

Abstract: It has been demonstrated that food intake and reproductive physiology are both simultaneously modulated to optimize reproductive success under fluctuating metabolic conditions. Ghrelin (GHRL) is an orexigenic peptide identified as the endogenous ligand of the growth hormone secretagogue receptor that is being investigated for its potential role on reproduction. Considering that data available so far are still limited and characterization of GHRL action mechanism on the reproductive system has not been fully el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…On the other hand, the level of GHSR was found low in the endometrium of infertile women [261], which implies that a balanced level of ghrelin system is important for healthy reproduction. A recent study shows that ghrelin administration significantly decreases testosterone plasma levels and impairs spermatogenesis possibly by inhibition of the hypothalamic-pituitary-gonadal axis [262]. e majority of studies report that ghrelin inhibits testosterone production and spermatogenesis.…”
Section: Effect Of Ghrelin On Reproductive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the level of GHSR was found low in the endometrium of infertile women [261], which implies that a balanced level of ghrelin system is important for healthy reproduction. A recent study shows that ghrelin administration significantly decreases testosterone plasma levels and impairs spermatogenesis possibly by inhibition of the hypothalamic-pituitary-gonadal axis [262]. e majority of studies report that ghrelin inhibits testosterone production and spermatogenesis.…”
Section: Effect Of Ghrelin On Reproductive Systemmentioning
confidence: 99%
“…Another study on mice showed that genetic suppression of the GHSR1a in male mice attenuates the preference for female mice, sexual motivation, and interaction, by effects on DA neurotransmission [72]. After the hypothalamic ghrelin administration, the reproductive performance of male mice was found to decrease [262].…”
Section: Effect Of Ghrelin On Sexualmentioning
confidence: 99%
“…Indeed, 10-day long daily sc ghrelin injection decreased different cell types (except for spermatogonia), seminiferous tubules diameter and their germinal epithelium thickness [126]. Additionally, 42-day long treatment with ip injected ghrelin even led to reduced sperm concentration, motility, percentage of spermatogonia and sperm [118]. On the cellular level, sc injected ghrelin increased vacuolated mitochondria, reduced endoplasmic reticulum and intracellular organelles in the testis, and caused several detachment areas between cell membrane and its basement membrane [126].…”
Section: Testicular Morphologymentioning
confidence: 98%
“…In several other studies it was observed that circulating LH concentrations were reduced due to ghrelin administration in form of chronic sc injection of acyl or desacyl ghrelin in pubertal, adult [107] or food-restricted male rats [116], acute sc injection of acyl or desacyl ghrelin [107], bolus injection into the third cerebral ventricle of female sheep [117], 42 day long hypothalamic infusion in male mice [118], acute icv injection in female mice [103], as well as acyl ghrelin infusion in healthy men [104].…”
Section: Luteinizing Hormonementioning
confidence: 98%
“…Unlike leptin and insulin, ghrelin exhibits inhibition of GnRH/LH release and reproductive function (Furuta et al 2001a, Kluge et al 2013. Hypothalamic ghrelin administration impairs spermatogenesis in mice by inhibiting the HPG axis, thereby inhibiting reproductive function (Poretti et al 2018). Preclinical studies reported a delayed effect of ghrelin on puberty initiation and noted the inhibition of LH secretion in vivo by ghrelin (Martini et al 2006).…”
Section: Peripheral Metabolic Hormones Linking Energy/nutritional Sta...mentioning
confidence: 99%